2018
DOI: 10.7186/bgsm65201807
|View full text |Cite
|
Sign up to set email alerts
|

The reconstruction of 3D geo-lithological model of Pekan, Pahang: A possible onshore extension of Penyu Basin

Abstract: Well studies have confirmed the presence of Quaternary sediments in both onshore and offshore areas near the township of Pekan in Pahang, while the Tertiary sediments are only found offshore. This could be well-explained through the palaeo-environmental evolution of the Tertiary sediments in Penyu Basin, where it started from continental (older sediments) to marine (younger sediments) environments, suggesting that transgression had occurred causing the Pahang River delta to be located where it is today. In fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…More importantly, the gravity profile indicates that the Tertiary outcrops at Chenor clearly lie in a basin that is separated from the Penyu Basin by a regional basement high composed of a mixture of Palaeozoic metamorphic and Mesozoic plutonic rocks. This is confirmed by the groundwater boreholes in Figure 7 which penetrated pre-Tertiary basement comprising mainly weathered granites north of Pahang River and mainly metamorphic rocks south of it (Yoong et al, 2018). 5 showing the correlation with pre-Tertiary outcrop geology (lower panel).…”
Section: Mazlan Madonsupporting
confidence: 58%
See 4 more Smart Citations
“…More importantly, the gravity profile indicates that the Tertiary outcrops at Chenor clearly lie in a basin that is separated from the Penyu Basin by a regional basement high composed of a mixture of Palaeozoic metamorphic and Mesozoic plutonic rocks. This is confirmed by the groundwater boreholes in Figure 7 which penetrated pre-Tertiary basement comprising mainly weathered granites north of Pahang River and mainly metamorphic rocks south of it (Yoong et al, 2018). 5 showing the correlation with pre-Tertiary outcrop geology (lower panel).…”
Section: Mazlan Madonsupporting
confidence: 58%
“…This line, which is also above sea level, may be taken as the landward limit of the basin (Figure 4B). Yoong et al (2018) reported groundwater boreholes that were drilled through the Quaternary sediments in the Pekan area (red dots in Figure 3). The boreholes penetrated as much as 115 m of Quaternary sediments before reaching the bedrock of pre-Tertiary geology comprising weathered granites and metasediments.…”
Section: Basin Edgementioning
confidence: 99%
See 3 more Smart Citations